Mandi Balimau dalam Tradisi Kenduri Sko di Semurup sebagai Bentuk Interaksi Sosial Masyarakat Islam Nusantara: Pendekatan Interaksi Simbolik Max Weber - Nera Afriyanti (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2023)
Bathing Balimau is a communal bathing tradition carried out by all layers of the Semurup-Kerinci society every five to six years on the riverbank. The Bathing Balimau conducted during the Sko Celebration tradition in Semurup differs from Bathing Balimau in other areas due to its significance. Within this Bathing Balimau tradition are several elements whose meanings and functions are not yet understood. Therefore, this research aims to uncover the essence of the Bathing Balimau tradition in Semurup. Symbolic interactionism theory is employed in this study. Through the symbolic aspect, the elements within the Bathing Balimau tradition are examined to uncover its essence. One of these elements is the location of the Bathing Balimau process, which is carried out on the riverbank, holding its meaning and influencing the essence of the Bathing Balimau tradition. The importance of this tradition lies in its role as a means of purifying oneself, both externally and internally, as well as a form of social interaction.